Community Assistance in Producing Environmentally Friendly Mol Organic Waste Based on Banana Stems and Corm in Koya Koso Village, Abepura District, Jayapura Regency, Papua, Indonesia - Inrianti; Sumiyati Tuhuteru; Patras Pumoko; Geztha Nathan Kogoya (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Koya is one of the agricultural areas in the Jayapura region, Papua Province. It is expected to become a hub for horticultural crops in Papua. However, the current agricultural system needs improvement by utilizing liquid organic fertilizer known as MoL (Microorganism Local) or biofertilizer, which is environmentally friendly. The main ingredients of MoL are banana stems and corm, and coconut water is used as a substitute for water in the mixture. The goal of this community assistance project is to introduce MoL as an eco-friendly organic fertilizer with significant benefits for soil, plants, and human health. This activity was conducted in three stages: mediation and survey, socialization, and assistance in making MoL from banana stems and corm. The results showed a positive response from the farming community in Koya Koso, who adopted the organic and environmentally friendly farming system. The organic fertilizer is affordable and easy to make domestically. Further activities are recommended to apply MoL to vegetable crops cultivated by farmers in Koya Koso.